2016
DOI: 10.3389/fmicb.2016.00545
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of Three New Bacteriophages Useful in the Biocontrol of Salmonella

Abstract: Non-typhoid Salmonella is the principal pathogen related to food-borne diseases throughout the world. Widespread antibiotic resistance has adversely affected human health and has encouraged the search for alternative antimicrobial agents. The advances in bacteriophage therapy highlight their use in controlling a broad spectrum of food-borne pathogens. One requirement for the use of bacteriophages as antibacterials is the characterization of their genomes. In this work, complete genome sequencing and molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 50 publications
0
48
0
Order By: Relevance
“…Furthermore, the bacteriophage showed a delaying the growth of bacterial pathogens in wastewater, that belongs the high lytic activity on bacterial host. This study showed a significant reduction of bacterial growth with using phage cocktail another recent study showed using phage cocktail was more efficient with commercial applications in bacteriophage therapy against Salmonella (Bardina et al, 2016). As a result of all this, using phage cocktail has a great effect in bio-desorption, bioremediation of pollutants and recycling of wastewater (Gaikwad et al, 2014;Zhao et al, 2009).…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, the bacteriophage showed a delaying the growth of bacterial pathogens in wastewater, that belongs the high lytic activity on bacterial host. This study showed a significant reduction of bacterial growth with using phage cocktail another recent study showed using phage cocktail was more efficient with commercial applications in bacteriophage therapy against Salmonella (Bardina et al, 2016). As a result of all this, using phage cocktail has a great effect in bio-desorption, bioremediation of pollutants and recycling of wastewater (Gaikwad et al, 2014;Zhao et al, 2009).…”
Section: Discussionmentioning
confidence: 72%
“…tRNAs were detected using ARAGORN and tRNAscan-SE 3 ( Rombouts et al, 2016 ). The putative promoter sequences were predicted using the promoters online analysis tool Softberry 4 ( Bardina et al, 2016 ; Rombouts et al, 2016 ). The phage genome maps were drawn using Genome Diagram ( Pritchard et al, 2006 ).…”
Section: Methodsmentioning
confidence: 99%
“…UAB_Phi20 and UAB_Phi78 bacteriophages are members of the Podoviridae family with icosahedral heads (60 ± 1.5 nm and 66 ± 1.7, respectively) and short tails (13–14 nm) whereas UAB_Phi87 has also an icosahedral head (68 ± 2.7 nm) but a long contractile tail (114 ± 4.3 nm) and derives from the Myoviridae family11. The genomic features of the three bacteriophages have been recently published37. The bacteriophages were propagated in Salmonella Typhimurium LB5000 (SGSC181; University of Calgary).…”
Section: Methodsmentioning
confidence: 99%